2021
DOI: 10.1371/journal.pntd.0009304
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles secreted by Giardia duodenalis regulate host cell innate immunity via TLR2 and NLRP3 inflammasome signaling pathways

Abstract: Giardia duodenalis, also known as G. intestinalis or G. lamblia, is the major cause of giardiasis leading to diarrheal disease with 280 million people infections annually worldwide. Extracellular vesicles (EVs) have emerged as a ubiquitous mechanism participating in cells communications. The aim of this study is to explore the roles of G. duodenalis EVs (GEVs) in host-pathogen interactions using primary mouse peritoneal macrophages as a model. Multiple methods of electron microscopy, nanoparticle tracking anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…A recent study found that Giardia EVs trigger IL-1β, IL-6, and TNF-α secretion from mouse PMs via promoting the nuclear translocation of the NF-κB p65 subunit [ 53 ]. Another recent study identified TLR2 as a mediator for pyroptotic signaling in mouse PMs induced by Giardia EVs [ 25 ]. In contrast, our study revealed a significant increase of both TLR2 and TLR4 expression in Giardia -treated macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that Giardia EVs trigger IL-1β, IL-6, and TNF-α secretion from mouse PMs via promoting the nuclear translocation of the NF-κB p65 subunit [ 53 ]. Another recent study identified TLR2 as a mediator for pyroptotic signaling in mouse PMs induced by Giardia EVs [ 25 ]. In contrast, our study revealed a significant increase of both TLR2 and TLR4 expression in Giardia -treated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The VSPs of Giardia were reported to activate TLR2 and TLR4 in HEK293 cells [ 24 ]. The latest research has shown that Giardia extracellular vesicles (EVs) activate NLRP3 inflammasome signaling via TLR2 [ 25 ]. Growing evidence shows that activation of the NLRP3 inflammasome involves its deubiquitination or phosphorylation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Located on the cell membrane and in intracellular endosomes, TLRs can monitor and recognize a range of PAMPs derived from bacteria, parasites, viruses, and fungi. Importantly, studies have revealed the functions and mechanisms associated with the innate immune responses mediated by TLR2 and TLR4 during Giardia infection (Lee et al, 2014;Li et al, 2017;Serradell et al, 2019;Zhao et al, 2021). Additionally, it has been shown that the Plasmodium falciparum-derived metabolite, hemozoin, can activate TLR9 in host macrophages and DCs, leading to the massive secretion of proinflammatory factors and chemokines (Kawai and Akira, 2009;Kumar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Melting curves were analyzed following the PCR run to validate the homogeneity of PCR products. All the primers were synthesized by Sangon (Shanghai, China) and contained the following sequences: TLR9, 5 -CTGCCCAAACTCCACACTCT-3 forward primer and 5 -ACAAGTCCACAAAGCGAAGG-3 reverse primer (Zhao et al, 2021); and β-actin, 5 -TGCTGTCCCTGTATGCCTCT-3 forward primer and 5 -GGTCTTTACGGATGTCAACG-3 reverse primer (Li et al, 2017).…”
Section: Analysis Of Tlr9 Gene Expression By Reverse Transcriptase-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…The culture supernatants were collected and concentrated as previously described ( Zhao et al., 2021 ). Cell pellets were washed in ice-cold PBS and lysed with RIPA containing the protease inhibitor of phenylmethanesulfonyl fluoride (PMSF, 1 mM).…”
Section: Methodsmentioning
confidence: 99%